Application of electroosmosis for sludge dewatering — a review - Iwata, Masashi; Tanaka, Takanori; Jami, Mohammed Saedi (Taylor & Francis, 2013)
This work aims at providing an outline of engineering applications for electroosmosis, especially for sludge dewatering. A review of the theoretical analysis of electroosmotic dewatering is presented. The equations representing electroosmotic flow through porous media are initially discussed. Consolidation theory, which describes the progress of dewatering, is then described. In addition, various empirical research results addressing the effects of operational conditions and conditioning of sludge on both energy consumption and final water content of the sludge are reviewed. It is anticipated that this review will provide useful information to researchers pursuing solid–liquid separation of difficult-to-dewater materials such as sludge.